2012
DOI: 10.1051/epjconf/20123801001
|View full text |Cite
|
Sign up to set email alerts
|

Processes in massive nuclei reactions and the way to complete fusion of reactants. What perspectives for the synthesis of heavier superheavy elements?

Abstract: Abstract. By using the dinuclear system (DNS) model we determine the capture of reactants at the first stage of reaction, the competition between the DNS decay by the quasifission (QF) and the complete fusion (CF) process up to formation of the compound nucleus (CN) having compact shape. Further evolution of the CN is considered as its fission into two fragments or formation of evaporation residues (ER) by its cooling after emission of neutrons or/and charged light particles. Disappearance of the CN fission ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The moments of inertia and rotational alignment are sensitive to nuclear properties such as the pairing strength and to the specific orbitals active at the Fermi surface, thus systematic analysis of the moments of inertia can provide invaluable information on such properties. The recent experiment to study 256 Rf [31] provided new data which could be compared to that of 144 As has been noted previously, the rotational properties of the N =150 isotones are somewhat different, showing much faster alignment than the N =152 nuclei. It is interesting to question the differences in absolute value of the moments of inertia in these nuclei.…”
Section: Moments Of Inertia and Rotational Alignmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moments of inertia and rotational alignment are sensitive to nuclear properties such as the pairing strength and to the specific orbitals active at the Fermi surface, thus systematic analysis of the moments of inertia can provide invaluable information on such properties. The recent experiment to study 256 Rf [31] provided new data which could be compared to that of 144 As has been noted previously, the rotational properties of the N =150 isotones are somewhat different, showing much faster alignment than the N =152 nuclei. It is interesting to question the differences in absolute value of the moments of inertia in these nuclei.…”
Section: Moments Of Inertia and Rotational Alignmentsmentioning
confidence: 99%
“…Several studies suggested the possibility of using symmetric reactions (with a view to using neutron-rich Xe or Sn beams in a future radioactive beam facility) see e.g. [139,140,141,142,143,144,145,146]. The predicted cross sections are in some cases controversial and can differ by several orders of magnitude.…”
Section: Prospects and Future Perspectivesmentioning
confidence: 99%
“…Heavy-ion collisions combine the rich dynamics of a many-body out-of-equilibrium open quantum system with the complexities of the residual part of the strong interaction which leaks out of the small, but neither fundamental or point-like, nucleons, causing them to stick loosely together some of the time, and to fall apart at others. Understanding heavy-ion reactions across all energy scales is necessary to understand stellar nucleosynthesis [1], the synthesis of superheavy nuclei [2,3], the properties of nuclear matter [4][5][6], the QCD phase diagram [7,8] as well as the understanding of reaction mechanisms themselves [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This review surveys these studies in low energy heavy-ion reactions, finding significant effects on observables from the form of the spin-orbit interaction, the use of the tensor force, and the inclusion of time-odd terms in the density functional.Heavy-ion collisions combine the rich dynamics of a many-body out-of-equilibrium open quantum system with the complexities of the residual part of the strong interaction which leaks out of the small, but neither fundamental or point-like, nucleons, causing them to stick loosely together some of the time, and to fall apart at others. Understanding heavy-ion reactions across all energy scales is necessary to understand stellar nucleosynthesis [1], the synthesis of superheavy nuclei [2,3], the properties of nuclear matter [4][5][6], the QCD phase diagram [7,8] as well as the understanding of reaction mechanisms themselves [9][10][11][12][13].Among the theoretical techniques used to study heavy-ion reactions, methods based on timedependent Hartree-Fock have recently achieved the status of having sufficiently mature implementations free of limiting approximations, and running at a suitable speed, such that systematically varying the effective interaction in the calculations is possible. It is such studies that form the main subject of the present review.…”
mentioning
confidence: 99%
“…In fact, this assumption is completely doubtful because the yield of mass symmetric fragments produced by the quasifission and fast fission processes are competitive and often some orders of magnitude higher than the ones produced by the fusion-fission process (see for example, refs. [16,31].…”
Section: Discussion On the P Cn Resultsmentioning
confidence: 99%